2016
DOI: 10.21010/ajtcam.v14i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Mangiferin on Helicobacter Pylori-Induced Inflammation in Human Gastric Carcinoma Ags Cells

Abstract: Background: Gastric cancer is a serious health issue caused by H. pylori and claims more lives in developing and undeveloped countries. Hence, the need for a natural drug with several pharmacological activities with no adverse effect are highly recommended. The target of this study was to verify the anti-H. pyloric efficacy of mangiferin (MF) on H. pyloriinfected AGS cells. Materials and methods: AGS cells were co-cultured with H. pylori and incubated with increased concentration of MF (10, 20, 50 and 100 µg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Zhang and Yue demonstrated that mangiferin has the ability to eradicate H. pylori and concurrently inhibit multiple inflammatory markers including NF-Кβ subunit p65, IL-1β, IL-8 and TNF-α . In addition, the protein expression of inflammatory enzymes as COX-2 and iNOS were remarkably down-regulated in cultured human gastric carcinoma AGS cells following incubation with mangiferin [45]. The researchers concluded that mangiferin significantly downregulated the adhesion and invasion process as well as deactivated NF-p65, thereby blocking the inflammatory response and thus reducing the incidence of gastric carcinoma [45].…”
Section: Anti-inflammatory Benefits Of Mangiferinmentioning
confidence: 98%
See 1 more Smart Citation
“…Zhang and Yue demonstrated that mangiferin has the ability to eradicate H. pylori and concurrently inhibit multiple inflammatory markers including NF-Кβ subunit p65, IL-1β, IL-8 and TNF-α . In addition, the protein expression of inflammatory enzymes as COX-2 and iNOS were remarkably down-regulated in cultured human gastric carcinoma AGS cells following incubation with mangiferin [45]. The researchers concluded that mangiferin significantly downregulated the adhesion and invasion process as well as deactivated NF-p65, thereby blocking the inflammatory response and thus reducing the incidence of gastric carcinoma [45].…”
Section: Anti-inflammatory Benefits Of Mangiferinmentioning
confidence: 98%
“…In addition, the protein expression of inflammatory enzymes as COX-2 and iNOS were remarkably down-regulated in cultured human gastric carcinoma AGS cells following incubation with mangiferin [45]. The researchers concluded that mangiferin significantly downregulated the adhesion and invasion process as well as deactivated NF-p65, thereby blocking the inflammatory response and thus reducing the incidence of gastric carcinoma [45]. Interestingly, in several other studies, mangiferin has demonstrated inhibitory activity against Helicobacter pylori-induced inflammatory responses in the gastrointestinal tissues and gastrointestinal toxicity [42][43][44]46].…”
Section: Anti-inflammatory Benefits Of Mangiferinmentioning
confidence: 98%
“…Furthermore, MAG is also effective for preventing the production of hydroxyl radicals in the Fenton-type reaction (20). Previous researchers had proved that MAG has many other physiologic and pharmacological effects, such as anti-inflammatory (21), antidiabetic (22), anti-cancer (23), inhibition of osteoclast differentiation (24), and so on. However, the effects of MAG on autophagy and hypertrophic chondrocyte differentiation have not been studied.…”
mentioning
confidence: 99%
“…3 ). Mangiferin showed MIC 600 µg/mL against Helicobacter pylori as reported by Zhang and Yue (2017) . Khumpook et al (2018) demonstrated the antibacterial potential of three varieties of mango leaves against S. epidermidis, S. aureus, Methicillin-resistant S. aureus, P. acnes and P. aeruginosa .…”
Section: Discussionmentioning
confidence: 54%